Oh, boy! Babies! - Herzig, Alison Cragin; Mali, Jane Lawrence; Thomas, Katrina (Boston : Little, Brown, 1980)
A photo essay of a class in infant care given to fifth and sixth grade boys with the help of mothers and real babies.
Keywords: Babysitting -- Juvenile literature; Infants -- Care -- Juvenile literature; Babysitters; Babies -- Care